2011
DOI: 10.1590/s1679-45082011rc1885
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac tamponade due to peripheral inserted central catheter in newborn

Abstract: This article reports the case of an adverse event of cardiac tamponade associated with central catheter peripheral insertion in a premature newborn. The approach was pericardial puncture, which reversed the cardiorespiratory arrest. The newborn showed good clinical progress and was discharged from hospital with no complications associated with the event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In accordance with our findings, da Silva Dornaus et al also reported a preterm neonate (30 weeks) with cardiac tamponade secondary to PICC [8]. The neonate showed episodes of bradycardia, low O 2 saturation, cyanosis, dyspnea, and worsening of clinical condition 5 days after PICC insertion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with our findings, da Silva Dornaus et al also reported a preterm neonate (30 weeks) with cardiac tamponade secondary to PICC [8]. The neonate showed episodes of bradycardia, low O 2 saturation, cyanosis, dyspnea, and worsening of clinical condition 5 days after PICC insertion.…”
Section: Discussionsupporting
confidence: 92%
“…Radiography and echocardiography examinations revealed that the tip of the catheter was in the cardiac chamber with pericardial effusion and signs of tamponade. These authors also reported improvement in the neonate's clinical situation after immediate cardiac puncture and extraction of 25 mL of fluid similar to the infused solution [8].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation